Upaya kerjasama Indonesia-Prancis dalam Meningkatkan Pariwisata Indonesia Melalui Third Joint Working Group on Tourism (JWG) tahun 2016-2018 - Sari, Kendalita (Global and Policy Journal of International Relations, 2021)
Abstract In international relation, a nation constantly needs help from other countries. A country that wants to support other nation must have a strength of nation’s institution and enormous resources. This study recovers the conditions and the opportunities of Indonesia tourism. In order to develop Indonesia tourism sector, Indonesia has strategic partnership with France. An analysis of developing Indonesia tourism, the Indonesian government not only uses government-to-government relations, but also by evaluating non-government organisations, multi-track diplomacy by cooperating with private actors, and using public diplomacy to understand culture and behavior from each nation. Through this Joint Working Group on Tourism, hopefully this project will contribute to expand Indonesia particularly on tourism sector. Keywords: Tourism Cooperation, Strategic Partnership, Joint Working Group on TourismDalam hubungan internasional, suatu negara pasti membutuhkan bantuan dari negara lain. Hal ini didasarkan karena negara pemberi bantuan memiliki keunggulan dalam sumber daya, dan kekuatan negaranya Tulisan ini akan memaparkan mengenai bagaimana kondisi dan peluang yang dimiliki pariwisata Indonesia. Untuk membangun sektor pariwisatanya, Indonesia melalui kemitraan strategis dengan Perancis melakukan beberapa strategi. Dalam prakteknya, Indonesia tidak selalu melakukan hubungan pemerintah ke pemerintah, Indonesia menggunakan multi track diplomasi dengan menggandeng aktor swasta, dan menggunakan diplomasi publik untuk memahami budaya, perilaku, dan mengatur hubungannya dengan negara lain dalam rangka meningkatkan serta perluasan pasar bagi pariwisata Indonesia. Melalui Joint Working Group On Tourism ini diharapkan menghasilkan peningkatan pariwisata bagi Indonesia. Kata Kunci:Kerja Sama Pariwisata, Kemitraan Strategis, Joint Working Group on Tourism  DOI : https://doi.org/10.33005/jgp.v9i2.3006